Ethical Risks of Environmental Policies: The Case of Ethanol in North America - S. M. Jordaan; Michal C. Moore (The School of Public Policy Publications, 2010)
Policy to address the environmental impacts of transportation fuel derived from conventional oil is frequently focused on the promotion of alternatives such as biofuels. While there are some biofuels that can be developed with relatively few impacts, others can result in broader, complex social concerns that should be included in the policy debate. These concerns include impacts arising from the conversion of natural landscapes and changes in food supply. To help inform policy development, this paper raises a series of questions to encourage a fuller debate and proposes a methodology to capture ethical risks related to the energy and environmental choices. This methodology should be applied to policies that encourage a transition to fuel alternatives for transportation – whether unconventional fossil fuels or corn ethanol. Energy